-47=7+6x

Simple and best practice solution for -47=7+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -47=7+6x equation:


Simplifying
-47 = 7 + 6x

Solving
-47 = 7 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-47 + -6x = 7 + 6x + -6x

Combine like terms: 6x + -6x = 0
-47 + -6x = 7 + 0
-47 + -6x = 7

Add '47' to each side of the equation.
-47 + 47 + -6x = 7 + 47

Combine like terms: -47 + 47 = 0
0 + -6x = 7 + 47
-6x = 7 + 47

Combine like terms: 7 + 47 = 54
-6x = 54

Divide each side by '-6'.
x = -9

Simplifying
x = -9

See similar equations:

| 6x=4(x+1)+2x-6 | | a+b=-2 | | 9=-4(2-7x)-5x | | 3/4(8x-12)=0 | | -4(2-7x)-5x=9 | | -6(x+3)+4x+7=5x+8 | | -1(x-27)+3(x+3)=9(x-3) | | 3.4x-1.32=2.04-2.2x | | 9x+9=30 | | 4x+7=30/x | | 14m+9-6m=8m+9 | | (1/6)(8x-7)=(x+7)/12 | | x+3+8x=2x-1 | | 5y+3(y-6)=3(y+2)-2 | | 3x+7=8x-13 | | (1/6)(8x-7)=(x+7/12) | | 2a-5b=38 | | -1(x-12)+2(x+3)=6(x+3) | | 6[9-(-3x-3)]=54x+108 | | P=c+3b+4aforc | | 7(4x-5)-3=28x-38 | | 8z-19=-15+7z | | 9x+8-7(x+1)=6x+4 | | -1(x-12)+2(x+3)=x+3 | | 4x=34+3x-5+7x | | 9x+1=9(x+9) | | 4x+9-67(x+1)=6x+7 | | x^3+3x^2-81x-85=0 | | -(7y+5)-(-6y-8)=0 | | (4/10x)-2x+(8/5)=(4/5) | | x/2-4=x/5-1 | | 87*28/29*4/9 |

Equations solver categories